Analysis of Tissue and Circulating Tumor DNA by Next Generation Sequencing of Hepatocellular Carcinoma: Implications for Targeted Therapeutics - Ikeda, Sadakatsu (Mol Cancer Ther, 2018)
Hepatocellular carcinoma (HCC) has limited treatment options. Molecular analysis of its mutational landscape may enable the identification of novel therapies. However, biopsy is not routinely performed in HCC. The utility of analyzing cell-free circulating tumor DNA (ctDNA) by next-generation sequencing (NGS) is not established. We performed 32 ctDNA NGS analyses on 26 patients; 10 of these patients had tissue NGS (236 to 626 genes). ctDNA was evaluated using an assay that detects single nucleotide variants, amplifications, fusions, and specific insertion/deletion alterations in 54 to 70 genes. The ctDNA demonstrated that 23 of 26 patients (88.5%) had ≥ 1 characterized alteration, and all these individuals had ≥ 1 potentially actionable alteration. The most frequently mutated gene was TP53 (16 of 26 patients, 61.5%). There were 47 unique characterized molecular alterations amongst 18 total gene alterations (variants of unknown significance (VUSs) excluded). ctDNA and tissue NGS frequently showed different profiles, perhaps due to length of time between tissue and blood samples (median = 370 days (range, 29 to 876 days)). Serial ctDNA evaluation in an illustrative patient treated with capecitabine demonstrated emergence of a new TP53 alteration after progression. In conclusion, ctDNA profiling is feasible in advanced HCC, and serial assessment using ctDNA NGS can reveal genomic changes with time. NGS of ctDNA provides a minimally invasive alternative for identifying potentially actionable gene alterations and potential molecular targeted therapies. Dynamic changes in molecular portfolio associated with therapeutic pressure in difficult-to-biopsy patients can be observed.